Informal education – essential source of continuous professional development of librarians (Confluenţe Bibliologice, 2023)
This article provides information about the professional skills training of specialized library staff, which can also be achieved through informal education, recognized as one of the most effective ways to develop skills for identifying, analyzing and exploiting informational resources. In the Scientific Library of the USARB, informal education is presented through a wide range of events, which increase the degree of personal and professional development of librarians through their educational, scientific and cultural content.
Keywords: formal education; non-formal education; informal education; professional skills